2022
DOI: 10.3390/su141610100
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Life Cycle Assessment of Palm Kernel Shell in Ceramic Tile Production: Managerial Implications for Renewable Energy Usage

Abstract: The palm oil industry is a promising biomass source, as the production generates wastes more than four times that of the main product. In 2020, for 45 MT of crude palm oil production in Indonesia, it was estimated that around 12 MT of palm kernel shell were generated or equivalent to 5.4 MTOE in net calorific value. This high calorific value of solid waste can be used by industries as a source of renewable energy, once it is proven to be technically, environmentally and economically feasible. In this comparati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
0
0
0
Order By: Relevance
“…In recent years, Life Cycle Assessment (LCA) has been the most commonly used scientific tool to quantify the environmental impacts of processes and products [17,18]. LCA has been extensively applied to biomass pyrolysis [19][20][21][22] with the aim of quantifying its environmental impacts, and there are several reviews in the literature that draw together the key conclusions and recommendations for LCA's application in biomass pyrolysis. Yu et al [23] concluded that pine biomass is the best in terms of Global Warming Potential, but there is a lack of LCA studies to have considered its further environmental impacts.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, Life Cycle Assessment (LCA) has been the most commonly used scientific tool to quantify the environmental impacts of processes and products [17,18]. LCA has been extensively applied to biomass pyrolysis [19][20][21][22] with the aim of quantifying its environmental impacts, and there are several reviews in the literature that draw together the key conclusions and recommendations for LCA's application in biomass pyrolysis. Yu et al [23] concluded that pine biomass is the best in terms of Global Warming Potential, but there is a lack of LCA studies to have considered its further environmental impacts.…”
Section: Introductionmentioning
confidence: 99%